The Effectiveness of Storytelling and Roleplaying Media in Enhancing Early Childhood Empathy - Suryani, Ratna; Pranoto, Sugiyo; Astuti, Budi (Journal of Primary Education, 2020)
Kindergarten children’s still have difficulty to work in a team. Some of them still focus on their own activities without regard to their friends. This shows that there are deficiencies in the learning process so that children empathy does not yet develop. The purpose of this study was to examine the effectiveness of storytelling and roleplaying media in increasing empathy skills of kindergarten students. The research method was a quasi-experimental design. The subject was kindergarten students who were within the age range of 5-6 in Genuk district in which samples were 31 students as the experimental class and 21 students as the control class. The data analysis technique used descriptive analysis, paired t-test, and independent t-test. The results showed that the storytelling and roleplaying media could significantly increase empathy of early childhood (AUD), the average score of AUD social empathy of the experimental class was higher than that of the control class and 32.46% of AUD social empathy in the experimental class was in the Developing as Expected (BSH). Therefore, it could be concluded that the application of storytelling and roleplaying method was effective in increasing social empathy skills compared to the application of storytelling media only.